The relational state: Beyond marketisation and managerialism. Issue 4 (March 2014) - Muir, Rick
<x xml:space="preserve">Abstract</x> Our public services, whether driven by the state or market forces, are not fit to tackle many of the complex, long‐term problems facing Britain today. Rick Muir describes a revolution in thinking about public services, focused on accountability to and empowerment of service users and their local communities.